2007
DOI: 10.1002/pip.770
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on cost and life‐cycle analysis for 100 MW very large‐scale PV (VLS‐PV) systems in deserts using m‐Si, a‐Si, CdTe, and CIS modules

Abstract: This paper is a study of comparisons between five types of 100 MW Very Large‐Scale Photovoltaic Power Generation (VLS‐PV) Systems, from economic and environmental viewpoints. The authors designed VLS‐PV systems using typical PV modules of multi‐crystalline silicon (12·8% efficiency), high efficiency multi‐crystalline silicon (15·8%), amorphous silicon (6·9%), cadmium tellurium (9·0%), and copper indium selenium (11·0%), and evaluated them by Life‐Cycle Analysis (LCA). Cost, energy requirement, and CO2 emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 4 publications
1
87
1
1
Order By: Relevance
“…Many of the most favourable locations for solar PV lie in sparsely inhabited regions. For example, Ito et al (2008) assumed that 100 km of transmission lines would be required to connect a 100-MW PV system to existing transmission, and found that transmission infrastructure comprised between ∼ 10 and 15% of system CED over the lifetime of the project (Ito et al 2008 , Table 8). Furthermore, Ito et al (2005) estimated losses due to transformer, reactive power compensation and transmission line losses of 5.8-8.2% for a 100 km line in a hot desert.…”
Section: Transmission Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…Many of the most favourable locations for solar PV lie in sparsely inhabited regions. For example, Ito et al (2008) assumed that 100 km of transmission lines would be required to connect a 100-MW PV system to existing transmission, and found that transmission infrastructure comprised between ∼ 10 and 15% of system CED over the lifetime of the project (Ito et al 2008 , Table 8). Furthermore, Ito et al (2005) estimated losses due to transformer, reactive power compensation and transmission line losses of 5.8-8.2% for a 100 km line in a hot desert.…”
Section: Transmission Infrastructurementioning
confidence: 99%
“…As such, high-voltage transmission infrastructure is usually assumed to lie outside the study boundary for electricity generation NEA [for exceptions, see Ito et al (2008Ito et al ( , 2016]. …”
Section: Transmission Infrastructurementioning
confidence: 99%
“…[12] 1997 PV Japan Process [13] 1997 PV US Process [14] 2000 PV Unspecified Process [15] 2001 PV Europe Process [16] 2001 PV US Process [17] 2002 PV India Process [18] 2002 PV Europe Process [19] 2004 PV Europe Process [20] 2004 PV India Process [21] 2004 PV Europe Process [22] 2005 PV Europe Process [23] 2006 PV US Process [24] 2006 PV Europe Process [25] 2006 PV US Process [26] 2006 PV Singapore Process [27] 2007 PV Europe Process [28] 2007 PV US Process [29] 2007 PV Europe Process [30] 2008 PV China Process [31] 2008 PV Many Process [32] 2009 PV Europe Process [33] 2009 PV US Process [34] 2009 PV Europe Process [6] 2010 PV US/Canada Process [35] 2010 PV US Hybrid [36] 2010 PV China/Japan Process [37] 2011 PV Europe Process [38] 2011 PV Europe Process [39] 1990 CSP US I-O [40] 1999 CSP Australia Hybrid [41] 2002 CSP Australia Hybrid [42] 2008 CSP Europe Process [43] 2011 CSP US Hybrid [44] 2011 CSP Europe Process [45] 2011 CSP Chile Process [46] 2011 CSP China Process …”
Section: Literature Search and Screeningmentioning
confidence: 99%
“…By optimizing the system performance based only on GHG emissions, new environmental burdens may be introduced from other environmental emissions (e.g., NO x and SO 2 ). A holistic or system-level perspective is therefore essential in the assessment, and the range of emission types included in a study may critically affect the outcome; although described as "full LCA studies", some studies (e.g., [16][17][18]) include only GHG emissions. Overall emissions can be categorized into direct emissions (e.g., from the stack of a power plant) and indirect emissions (e.g., related either to upstream provision of fuel, resources, goods, etc.…”
Section: Introductionmentioning
confidence: 99%